Functionalising the azobenzene motif delivers a light-responsive membrane-interactive compound with the potential for photodynamic therapy applications1. Issue 29 (7th August 2015) - Hester, Theodore J.; Dennison, Sarah R.; Baker, Matthew J.; Snape, Timothy J.
<x xml:space="preserve">Abstract</x> A light-responsive azobenzene derivative provides a membrane-interactive compound with the potential for photodynamic therapy applications.